Implementasi Augmented Reality Bangunan Cagar Budaya Kota Palopo Berbasis Android - Rudianto Nursalim (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
Augmented reality (AR) is a technology that combines virtual 3D objects or objects into a real-time display of a world. Augmented reality is not like virtual reality, which completely replaces what is in the real world but only adds to or complements it. as is the case with drawing or creating 3D objects for cultural heritage buildings in the city of Palopo, especially the old Djami mosque and the Pniel church in the city of Palopo. It is known that the buildings of the Djami mosque and the Pniel Church in the city of Palopo are more than a century old. Augmented Reality (AR) technology in the application of the implementation of augmented reality Cultural Heritage Buildings of the City of Palopo can make it easier for the public to see the cultural heritage buildings of the city of Palopo, especially the old Djami mosque and the Pniel Church of Palopo City. Building objects can be replaced with markers or images. Markers are patterns made in the form of 2D images that will be recognized by the camera. By utilizing the Augmented Reality (AR) technique, the people of the city of Palopo can find out about the cultural heritage of the city, and this application can be used anywhere and anytime. The software used in building this AR application uses Blender 3D, Vuforia, Unity 3D, and Visual Studio 2019. Keywords— Augmented Reality, Cultural Heritage, Android